Isolation of wild-type yeasts from natural sources for bioethanol production, their characterization and the effect of mineral salts on ethanol productivity in molasses - Kamal, Wasif (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.